The effect of risperidone on reward‐related brain activity is robust to drug‐induced vascular changes. Issue 9 (5th March 2021) - Hawkins, Peter C. T.; Zelaya, Fernando O.; O'Daly, Owen; Holiga, Stefan; Dukart, Juergen; Umbricht, Daniel; Mehta, Mitul A.
Abstract: Dopamine (DA) mediated brain activity is intimately linked to reward‐driven cerebral responses, while aberrant reward processing has been implicated in several psychiatric disorders. fMRI has been a valuable tool in understanding the mechanism by which DA modulators alter reward‐driven responses and how they may exert their therapeutic effect. However, the potential effects of a pharmacological compound on aspects of neurovascular coupling may cloud the interpretability of the BOLD contrast. Here, we assess the effects of risperidone on reward driven BOLD signals produced by reward anticipation and outcome, while attempting to control for potential drug effects on regional cerebral blood flow (CBF) and cerebrovascular reactivity (CVR). Healthy male volunteers ( n = 21) each received a single oral dose of either 0.5 mg, 2 mg of risperidone or placebo in a double‐blind, placebo‐controlled, randomised, three‐period cross‐over study design. Participants underwent fMRI scanning while performing the widely used Monetary Incentive Delay (MID) task to assess drug impact on reward function. Measures of CBF (Arterial Spin Labelling) and breath‐hold challenge induced BOLD signal changes (as a proxy for CVR) were also acquired and included as covariates. Risperidone produced divergent, dose‐dependent effects on separate phases of reward processing, even after controlling for potential nonneuronal influences on the BOLD signal. These data suggest the D2 antagonist risperidone has a wide‐ranging influence on DA‐mediated reward function independent of nonneuronal factors. We also illustrate that assessment of potential vascular confounds on the BOLD signal may be advantageous when investigating CNS drug action and advocate for the inclusion of these additional measures into future study designs. Abstract : Single dose risperidone produces dose‐response and divergent effects on different phases of reward‐related brain activity in healthy human volunteers in a placebo‐controlled fMRI study. These effects persist after accounting for potential nonneuronal effects of the drug on cerebral blood flow and cerebrovascular reactivity (as measured by a breath hold challenge).